Activation of Fas/FasL pathway and the role of c-FLIP in primary culture of human cholangiocarcinoma cells. Issue 1 (December 2017) - Carnevale, Gianluca; Carpino, Guido; Cardinale, Vincenzo; Pisciotta, Alessandra; Riccio, Massimo; Bertoni, Laura; Gibellini, Lara; De Biasi, Sara; Nevi, Lorenzo; Costantini, Daniele; Overi, Diletta; Cossarizza, Andrea; et al.
Abstract Intrahepatic cholangiocarcinoma (iCCA) represents a heterogeneous group of malignancies emerging from the biliary tree, often in the context of chronic bile ducts inflammation. The immunological features of iCCA cells and their capability to control the lymphocytes response have not yet been investigated. The aims of the present study were to evaluate the interaction between iCCA cells and human peripheral blood mononuclear cells (PBMCs) and the role of Fas/FasL in modulating T-cells and NK-cells response after direct co-culture. iCCA cells express high levels of Fas and FasL that increase after co-culture with PBMCs inducing apoptosis in CD4+, CD8+ T-cells and in CD56+ NK-cells.In vitro, c-FLIP is expressed in iCCA cells and the co-culture with PBMCs induces an increase of c-FLIP in both iCCA cells and biliary tree stem cells. This c-FLIP increase does not trigger the caspase cascade, thus hindering apoptotis of iCCA cells which, instead, underwent proliferation. The increased expression of Fas, FasL and c-FLIP is confirmedin situ, in human CCA and in primary sclerosing cholangitis. In conclusion our data indicated that iCCA cells have immune-modulatory properties by which they induce apoptosis of T and NK cells, via Fas/FasL pathway, and escape inflammatory response by up-regulating c-FLIP system.